IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN FISIKA MENURUT PERSEPSI SISWA SMA NEGERI DI KOTA PALU - Nurhaeni; Werdhiana, I Komang (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This research is quantitative descriptive. This study aims to describe the implementation of the scientific approach in physics subjects according to the perceptions of state high school students in Palu City. The instrument used in this study was a questionnaire given to 102 students spread across 4 public high schools in Palu City. The results of this study indicate that the scientific approach as a whole has been implemented with an average value of 80.44 and the respondents who stated that the scientific approach has been implemented were obtained by 77.45% and based on the categorization of the statement items it was included in the implemented category but from the five phases: observing, asking, trying, associating and communicating in their respective applications also still have shortcomings that need to be improved.